The physiopathology of angina pectoris. - da Costa, J T (1997)
The author reviews the pathophysiology of angina pectoris. The first part concerns to the regulation of coronary blood flow: 1. Determinants of myocardial oxygen consumption (preload, afterload,contractility, heart rate); 2. Factors that control the myocardial oxygen supply (perfusion pressure, coronary vascular resistance). The second part concerns the coronary insufficiency and its clinical consequences (angina pectoris, myocardium infarction, heart failure, arrhythmias, primary cardiac arrest. The third part concerns the principal pathophysiologic mechanisms of the stable angina and of the unstable angina (progression of atherosclerosis, platelet aggregation, thrombosis and/or alterations in vasomotor tone).